The role of the marketing complex in the management of the enterprise in market competition (Economics and region, 2022)
The problems of finding the optimal ways of enterprise development, improving their marketing activities in the conditions of turbulent changes in the external environment are considered. In order to ensure stable and efficient operation of enterprises, it is necessary to develop and improve marketing activities in enterprises, or delegate these functions to marketing outsourcing companies, which will be able to ensure the organization and implementation of marketing activities of enterprises. This is an extremely important task, as it will strengthen the market position of enterprises and increase their competitiveness, which in turn will have a positive impact on the development of Ukraine's economy as a whole. It was found that marketing is one of the most important and effective tools to increase the efficiency of enterprises. This is facilitated by the work of marketing services, which work in the following areas: first, marketing services explore the various aspects of the market that the company faces in the process of operation, and secondly, develops and implements tactics of market behavior. It is determined that the role of marketing is also that its tools – the only factor influencing consumer behavior to stimulate sales of its own products. Thus, it can be formed and implemented directly by the enterprise. It is investigated that functions act as means of realization of marketing activity. They have a significant impact on the formation and definition of strategic activities of the marketing department at the enterprise and its main tasks. There are four main blocks of marketing functions: analytical, production, sales and management function. This is facilitated by the work of marketing services that work in the following areas: first, marketing services explore different aspects of the market that the company faces in the process of operation, and secondly, develops and implements tactics of market behavior. The role of marketing is also that its tools – the only factor influencing consumer behavior to stimulate sales of its own products. Thus, it can be formed and implemented directly by the company. Functions are a means of marketing distance. They have a significant impact on the formation and determination of strategic activities of the marketing department at the enterprise and its main tasks. There are four main blocks of marketing functions: analytical, production, sales and management function.
Keywords: management; marketing; competitiveness; marketing activity; marketing mix